2008
DOI: 10.1007/s10562-008-9672-5
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Y Zeolite Supported CeO2 Catalysts for Deep Oxidation of 1, 2-Dichloroethane (DCE)

Abstract: Three Y zeolites supported CeO 2 catalysts (CeO 2 /USY, CeO 2 /HY, CeO 2 /SSY) were prepared and used for deep oxidation of 1,2-dichloroethane (DCE) in low concentration (about 1,000 ppm). The catalysts were characterized by XRD, N 2 adsorption/desorption and H 2 -TPR. The results showed that the catalytic activity of the supported CeO 2 catalysts was much higher than that of Y zeolites, in particular, CeO 2 /USY exhibited the highest activity, T 98% values of DCE was about 270°C. And the catalytic activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…2. The temperature was above 100 • C, eliminating the physisorption of NH 3 [20]. For pure CeO 2 , only one weak desorption peak was observed at about 150 • C [21], indicating that few weak acid sites were present.…”
Section: Nh 3 Temperature-programmed Desorptionmentioning
confidence: 96%
See 1 more Smart Citation
“…2. The temperature was above 100 • C, eliminating the physisorption of NH 3 [20]. For pure CeO 2 , only one weak desorption peak was observed at about 150 • C [21], indicating that few weak acid sites were present.…”
Section: Nh 3 Temperature-programmed Desorptionmentioning
confidence: 96%
“…The TPR signal of PC 9.6 Z located at 80 • C was weaker than that of PC 6.4 Z, indicating that the amount of CeO 2 loaded was beneficial for reduction. The peaks in the range of 350-450 • C were ascribed to the reduction of surface oxygen species, while the peaks above 600 • C were considered to represent the reduction of bulk Ce [20]. The two peaks shifted to a lower temperature and become narrower with increasing CeO 2 content, which was ascribed to an interaction between PdO and CeO 2 .…”
Section: Hydrogen Temperature-programmed Reductionmentioning
confidence: 99%
“…Gutiérrez-Ortiz and co-workers [21][22][23] have pointed out that ceria-zirconia mixed oxide with a proper combination of surface acidity and accessible lattice oxygen exhibit better activity for the decomposition of CVOCs than pure ceria/zirconia catalysts. In our previous study, we have found that the introduction of CeO 2 species to different types of zeolites Y (HY, USY and SSY) results in a certain synergy between CeO 2 species and zeolites Y, which shows a promotion in the catalytic activity for deep oxidation of CVOCs [24].…”
Section: Introductionmentioning
confidence: 95%
“…4(a)) demonstrates reduction peaks at about 520 o C and 750 o C due to surface and bulk reduction, respectively. 19) The relative peak intensity at 750 o C in pure ceria demonstrates that bulk oxygen reduction is the main process ( Fig. 4(a)).…”
Section: Resultsmentioning
confidence: 91%